The risk of venous thromboembolism in women with inflammatory bowel disease during pregnancy and the postpartum period: A systematic review and meta-analysis. Issue 38 (September 2019) - Kim, Yeon Hee; Pfaller, Birgit; Marson, Alanna; Yim, Hyeon Woo; Huang, Vivian; Ito, Shinya
Abstract : Abstract: Pregnancy and inflammatory bowel disease (IBD) are independent risk factors for venous thromboembolism (VTE). Nevertheless, the optimal VTE prevention strategy for women with IBD in pregnancy and postpartum period has not been established yet. We assessed VTE risks during pregnancy and the postpartum period in women with IBD through systematic review and meta-analysis. Systematic searches were conducted in MEDLINE (Ovid), Embase (Ovid), CENTRAL (Ovid), and Web of Science (Tomson Reuters) from the database inception till May 2017 to identify relevant studies reporting the risk of VTE during pregnancy and/or the postpartum period in women with IBD. Random effect meta-analyses were performed to compare VTE-related outcomes between women with IBD and without IBD. Our protocol was registered: CRD 42017060199 in the PROSPERO International prospective register of systematic reviews. In the analysis of 5 studies reviewed, IBD population (n = 17, 636) had a significantly increased risk of VTE during pregnancy (pooled risk ratio (RR) 2.13, 95% confidence interval (CI) 1.66–2.73) and postpartum (RR 2.61, 95% CI 1.84–3.69), comparing to the non-IBD population (n = 11, 251, 778). According to the location of VTE, the risk of deep vein thrombosis increased significantly by RR of 2.74 (95% CI 1.73–4.36) during pregnancy, whilst risk increase of pulmonary embolism was not statistically significant. In the subgroup analysis, the degree of VTE risk was higher in both periods in the UC group than in the CD group, as compared to that in the non-IBD population (UC group, during pregnancy: RR 2.24, 95% CI 1.6–3.11; postpartum period: RR 2.85, 95% CI 1.79–4.52). Significantly increased risks of VTE during pregnancy were found in the women with IBD, according to the periods and type of IBD, which might support a detailed strategy regarding administration of prophylactic anticoagulants to women with IBD. Abstract : Supplemental Digital Content is available in the text